Principles of analog electronics - Saggio, Giovanni (CRC Press, Taylor & Francis Group, 2014)
"The study of electronics requires the acquisition of certain prerequisites of fundamental concepts of mathematics, physics, chemistry, and the theory of circuits which are reviewed in this book before discussing electronics. The book is rich in illustrations, equations, tables, and homework problems (with accompanying solutions manual). Useful for undergraduate students, with the help of numerous tutorials, case studies, examples, the reader will be able to design a real electronic circuit"-- Provided by publisher.